Evaluasi Kesesuaian Lahan Untuk Tanaman Kacang Tanah Di Kelurahan Pardamean Kecamatan Rantau Selatan - Fitra Syawal Harahap (UNIVERSITAS LABUHANBATU, 2021)
Land evaluation is useful as a basis for sector development in an area that is useful for reorganizing existing land use so as to assist in making land use planning decisions. Peanuts have great potential to be cultivated and developed commercially because they have wide adaptability, high productivity, are resistant to plant pests and are more resistant to marginal conditions. This research is descriptive with survey methods. The sampling method used is based on land map units with a free grid system for data. climates classified by climate type Schimdt and Ferguson. Land evaluation was carried out using the matching method by matching and comparing land characteristics with land suitability class criteria so that to obtain land suitability classes for peanut plants in Rantau Selatan District, Labuhanbatu Regency, there were 6 sample points so that the determination of soil characteristics values for soil samples was carried out using a soil drill tool. at a depth of 0-60 cm. Research results for peanut plants in Pardamean Village, Rantau Selatan District according to marginal / S3. Land suitability for peanut plants cultivated in Rantau Selatan District Labuhanbatu Regency 2.017 ha. The actual land suitability class for peanut plants is Nwa, while the potential land suitability class is S2tcwa. Keywords: Land Evaluation, Peanut Plants, Rantau Selatan, Labuhanbatu